2013
DOI: 10.3382/ps.2013-03177
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational epigenetic effects on innate immunity in broilers: An underestimated field to be explored?

Abstract: Transgenerational epigenetics is becoming more and more important for understanding the variation of physiological responses of individuals to the environment and the inheritance of these responses based on all mechanisms other than the actual DNA nucleotide sequence. Transgenerational epigenetics is the phenomenon that the information of the environment of (usually) a female animal is translated into memory-like responses preparing the offspring. As a consequence, individuals of the next generation may show d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 103 publications
1
43
0
2
Order By: Relevance
“…As an important breeding animal, one broiler breeder hen produces approximately 100 broilers per year (Berghof et al., ). Furthermore, one breeder cock should mate with at least 8–10 breeder hens, which means that one breeder cock produces approximately 1,000 broilers per year.…”
Section: Introductionmentioning
confidence: 99%
“…As an important breeding animal, one broiler breeder hen produces approximately 100 broilers per year (Berghof et al., ). Furthermore, one breeder cock should mate with at least 8–10 breeder hens, which means that one breeder cock produces approximately 1,000 broilers per year.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that maternal nutrition can influence the growth and carcass traits of the progeny in chicken (An, Liu, Guo, & Sun, ; Callini & Sirri, ; Moraes et al., ). In birds, the maternal nutrition can directly affect offspring performance through incorporation of nutrients into the egg or triggering epigenetic modifications that regulate muscle progenitor cells (Berghof et al., ; Moraes et al., ). Studies have reported the existence of epigenetic effects in birds, and even indicate the possibility of epigenetic inheritance, although few studies evaluate the DNA methylation or the histone modification (Berghof et al., ; Feeney et al., ; Gao et al., ; Li et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant researches on poultry epigenetics (Berghof, Parmentier, & Lammers, ; Feeney, Nilsson, & Skinner, ; Frésard et al., ; Gao et al., ; Leurox et al., ; Li, Guo, Zhang, Gao, & Guo, ; Li et al., ) revealed that epigenetic modifications may occur from the first stage of egg, when the mother provides an environmental signature through the egg content (Frésard et al., ). However, studies approaching the transgenerational epigenetic variance estimation (Jablonka, ; Jablonka & Raz, ; Lopes, Bastiaansen, Janss, Knol, & Bovenhuis, ; Varona et al., ) for economically important traits are still scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Volgens Berghof et al (2013) Ook was er een effect van het ruw eiwitgehalte: vleeskuikens van moederdieren met gemiddeld of hoog ruw eiwitgehalte in het voer hadden de hoogste voeropname tussen 18 en 27 dagen leeftijd, en mannelijke vleeskuikens van moederdieren gevoerd met het laag eiwitniveau hadden het hoogste percentage borstvlees (van Emous, et al, 2015b).…”
Section: Transgenerationele Effectenunclassified